2020
DOI: 10.1007/s11030-020-10135-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential inhibitors of coronavirus hemagglutinin-esterase using molecular docking, molecular dynamics simulation and binding free energy calculation

Abstract: The pandemic outbreak of the Corona viral infection has become a critical global health issue. Biophysical and structural evidence shows that spike protein possesses a high binding affinity towards host angiotensin-converting enzyme 2 and viral hemagglutinin-acetylesterase (HE) glycoprotein receptor. We selected HE as a target in this study to identify potential inhibitors using a combination of various computational approaches such as molecular docking, ADMET analysis, dynamics simulations and binding free en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…To the best of our knowledge, there are currently no clinical reports that involve the use of silymarin against COVID-19; however, there are studies that suggest its potential use to combat this disease, as mentioned below. Taking into account the biophysical and structural evidence that spike proteins possess high binding affinity toward host ACE2 and the viral hemagglutinin esterase (HE) glycoprotein receptor, Patel et al ( 49 ) used a combination of various computational approaches to identify potential inhibitors of HE by employing the naturally occurring plant-based anticancer compound-activity-target database ( http://crdd.osdd.net/raghava/npact/ ). Subsequently, the best-scoring molecules were validated using molecular dynamics simulations and the authors identified silymarin (among other compounds) as a potential HE inhibitor with improved binding energy.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are currently no clinical reports that involve the use of silymarin against COVID-19; however, there are studies that suggest its potential use to combat this disease, as mentioned below. Taking into account the biophysical and structural evidence that spike proteins possess high binding affinity toward host ACE2 and the viral hemagglutinin esterase (HE) glycoprotein receptor, Patel et al ( 49 ) used a combination of various computational approaches to identify potential inhibitors of HE by employing the naturally occurring plant-based anticancer compound-activity-target database ( http://crdd.osdd.net/raghava/npact/ ). Subsequently, the best-scoring molecules were validated using molecular dynamics simulations and the authors identified silymarin (among other compounds) as a potential HE inhibitor with improved binding energy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SR-B1 could also potentially be a target for therapeutic designs. Patel et al have also suggested HE as a target ( 36 ) to inhibit the virus invasion mechanism.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…[25]. YASARA Structure (academic license) was employed for the docking experiment which comprised of water removal, the addition of polar hydrogens, steepest descent method was also used for the energy minimization [12].…”
Section: Data Set Preparationmentioning
confidence: 99%
“…The X-ray diffracted structure was fetched from Protein databank (PDB ID:6LU7; 2.16 Å resolution) which contains the single chain of 306 amino acids and co-crystal ligand N3 (N-[(5-methylisoxazol-3- [25]. YASARA Structure (academic license) was employed for the docking experiment which comprised of water removal, the addition of polar hydrogens, steepest descent method was also used for the energy minimization [12].…”
Section: Data Set Preparationmentioning
confidence: 99%
See 1 more Smart Citation